t(17;19) in Children with Acute Lymphocytic Leukemia: A Report of 3 Cases and a Review of the Literature - Katherine A. Minson; Pinki Prasad; Susan Vear; Scott Borinstein; Richard Ho; Jennifer Domm; Haydar Frangoul (Case Reports in Hematology)
Several cytogenetic abnormalities identified in patients with childhood acute lymphocytic leukemia (ALL) have been associated with a poor prognosis. There are several case reports in the literature describing t(17;19) in children with ALL. This translocation has been associated with hypercalcemia, coagulopathy, and poor outcome. We present three cases of ALL with t(17;19) treated at our institution and review the outcome of children reported in the medical literature.